How Large Are Global Energy Subsidies? - Coady, David; Parry, Ian.; Sears, Louis; Shang, Baoping (Washington, D.C. : International Monetary Fund, 2015)
This paper provides a comprehensive, updated picture of energy subsidies at the global and regional levels. It focuses on the broad notion of post-tax energy subsidies, which arise when consumer prices are below supply costs plus a tax to reflect environmental damage and an additional tax applied to all consumption goods to raise government revenues. Post-tax energy subsidies are dramatically higher than previously estimated, and are projected to remain high. These subsidies primarily reflect under-pricing from a domestic (rather than global) perspective, so even unilateral price reform is in countries' own interests. The potential fiscal, environmental and welfare impacts of energy subsidy reform are substantial.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet